2016
DOI: 10.3727/036012916x14533115160688
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Acupuncture at GV.4 Improves Functional Recovery in paralyzed rats after a Traumatic Spinal Cord Injury

Abstract: In the present study, the effect of electro-acupuncture (EA) on the oxidative stress, the spinal cord tissue preservation and the recovery of motor function was evaluated after a traumatic spinal cord injury (TSCI). Long Evans rats were randomized into five groups: 1. Sham; 2. TSCI without treatment; 3. TSCI + EA (acupoint GV.4); 4. TSCI + EA (acupoint GV.26) and 5.TSCI + EA (GV.4 + GV.26). The EA was performed with an Electro-Acupunctoscope, AWQ-104L Digital, wave dense-dispersed, current intensity 2.5mA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Macroscopically, the normal physiological function of the diseased muscle is affected, resulting in muscle tension. In the process of exerting its function, it is superior to the overall role of the muscle system and the support of biological forces, which will destroy the original balance of the skeletal system, aggravate the degeneration of the cervical vertebral body, and form a vicious circle [16].…”
Section: Etiology and Clinical Manifestations Of Cervicalmentioning
confidence: 99%
“…Macroscopically, the normal physiological function of the diseased muscle is affected, resulting in muscle tension. In the process of exerting its function, it is superior to the overall role of the muscle system and the support of biological forces, which will destroy the original balance of the skeletal system, aggravate the degeneration of the cervical vertebral body, and form a vicious circle [16].…”
Section: Etiology and Clinical Manifestations Of Cervicalmentioning
confidence: 99%
“…The results from a traumatic SCI model study showed that electroacupuncture at GV26 reduces radical hydroxyl concentration and increases lipid peroxidation. At the same time, stimulation of GV4 decreases oxidative stress and improves motor function recovery in the hind limbs of rats with paralysis, indicating electroacupuncture at GV4 could be a therapeutic alternative ( Juarez Becerril et al, 2015 ). Jiang et al found that electroacupuncture at Shuigou (DU26) and Fengfu (DU16) acupoints induce antioxidation effects by enhancing the SOD activity and decreasing the MDA level ( Jiang et al, 2014 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…The SEP incubation period of combination group was significantly lower than that of Jiaji EA group and ganglioside group (P < 0.05), indicating that Jiaji EA group and ganglioside ester treatment can better promote the regeneration and repair of injured nerves. Previous studies have shown that Jiaji EA has certain therapeutic effect on SCI in rats ( Sun, 1996 , Xu et al, 2006 , Juarez Becerril et al, 2015 )and ganglioside can promote the recovery of neurological function after SCI ( Constantini and Young, 1994 , Geisler et al, 1993 , Constantini and Young, 1994 , Donaldson et al, 2000 ). Our results further suggested that the combination of Jiaji EA and ganglioside ester effectively promoted the recovery of spinal cord nerve function in spinal cord rats.…”
Section: Discussionmentioning
confidence: 98%